Ferdinand Marcos: Exile, Fugitive or Prisoner? - David, Randolf S. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Thirty months have passe since the flight of the dictator to Hawaii. Yet he continues to be a thorn on the side of the Cory Aquino government. Today Filipinos are debating whether he should be allowed to return to the country he ruled for twenty years, even as the government alternates between letting the courts decide the legal grounds for denying or giving him travel documents, and invoking its political prerogative to keep him out of the country for as long as necessary.